Sistem Informasi Persediaan Barang untuk Pengelolaan Stok dan Distribusi - Arayan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2021)
The Inventory Information System is designed to streamline the process of managing and distributing goods. This system provides a user-friendly interface for tracking stock levels, managing orders, and overseeing the distribution of inventory. It enables staff to efficiently monitor inventory status, handle restocking processes, and maintain accurate records of all items. By integrating features such as real-time inventory tracking, automated alerts for low stock levels, and detailed reporting, the system enhances operational efficiency and accuracy. Additionally, it includes tools for generating comprehensive analytics, allowing management to make informed decisions based on real-time data. The system also supports integration with various supply chain management platforms, ensuring seamless coordination across all stages of inventory management. Overall, the Inventory Information System aims to improve the efficiency and accuracy of inventory control, contributing to smoother operations and better resource management.